Hubungan antara Dukungan Orang Tua dengan Motivasi Belajar Siswa Kelas Tinggi - Adnan K Adnan K; Ade Irma Agustriani; Muh. Idris Jafar (Universtas Negeri Makassar, 2022)
The problem in this study is the lack of parental support for children, so students lack motivation in learning. This research is a quantitative research with correlational type which aims to determine whether there is a significant relationship between parental support and student motivation. The sampling technique used is non-probability sampling technique. The results showed that parental support was in the very good category with a percentage of 87.52% and students' learning motivation was in the very good category with a percentage of 91.35%. The tcount (8,1307) is greater (>) the ttable value (1,98896) which means H0 is rejected and H1 is accepted. Thus, it can be concluded that there is a significant relationship between parental support and student motivation at SDN 17 Bila, Lalabata District, Soppeng Regency. The higher the parental support, the higher the student's learning motivation.